Estimation of Farmers’ Willingness-to-Pay for Quality Planting Material of Greater Yam (Dioscorea alata L.) - Sivakumar, P. Sethuraman; Nedunchezhiyan, M.; Adhiguru, P.; Jata, S. K. (Indian Journal of Extension Education, 2022)
Greater yam being a commercial tuber crop in Odisha state occupying a prominent place in food basket, the importance of meeting the planting material demand of the farmers, was realized by the ICAR-Central Tuber Crops Research Institute and initiated mass efforts to multiply the high-yielding and disease-resistant varieties of yam to supply to farmers as quality planting materials.. As the farmers’ willingness to pay for the planting material depends on their assessment of the utility of each attribute of it, a research investigation was carried out in Odisha to estimate the utility value of each yam planting material attribute from the farmers’ perspective. The utility values for each planting material attribute were estimated through a choice-based conjoint analysis. Results indicated that yield had the highest utility level (30 t/ha = 5.20 and 25 t/ha = 2.60), followed by planting material price (Rs. 30/kg = 1.147) and culinary quality (excellent quality = 0.794). The marginal WTP for the yield 30 t/ha versus 25 t/ha was Rs 4.54/kg. It clearly shows that the farmers were willing to pay an additional amount of Rs 4.54/kg for a quality yam planting material that gave a higher yield than their variety.
Keywords: Choice-based conjoint; Greater yam; Quality planting material